Instrumental observations of mass-wasting in the Mesters Vig district, northeast Greenland - Washburn, A. L. (Meddelelser om Grønland, 1967)
Quantitative observations of mass-wasting were carried out at a number of experimental sites in the Mesters Vig district of Northeast Greenland from 1956 to 1961. In addition to other data, the observations encompassed several thousand theodolite readings of cone targets that were inserted to alternate depths of 10 and 20 cm on diamicton slopes. The experimental sites ranged in mean gradient from 2.5° to 25° and had a spectrum of grain-size, moisture, and vegetational characteristics that permitted certain comparisons. The following are among the resulting conclusions. The first four are general; the remainder are specific for the Mesters Vig district. Frost creep and gelifluction can be quantitatively distinguished from each other. In gelifluction the influence of moisture can be more important than the influence of gradient or vegetation. Significant gelifluction probably occurs only at moisture values approximating or exceeding the Atterberg liquid limit. Frost creep and creep due to wetting and drying tend to be associated with a retrograde movement that reduces the amount of creep that would otherwise be present. Creep due to wetting and drying is of minor significance compared to frost creep. Frost creep in most places is due mainly to the annual freeze-thaw cycle rather than to short-term freeze-thaw cycles. Either frost creep or gelifluction can predominate in different places on the same slope, depending on variations in local conditions. At the sites investigated in most detail frost creep tends to exceed gelifluction but by not more, and probably less, than 3: 1 over a period of years, and either process can predominate in a given year. In "wet" areas there may be a straight-line relation between rate of mass-wasting and sine of gradient. Mass-wasting due to frost creep and gelifluction on a gradient of 10-14° ranged from a mean of 0.9 cm/yr in sectors subject to desiccation during summer, to a mean of 3. 7 cm/yr in sectors remaining saturated.